2019
DOI: 10.1039/c9ra03198g
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nucleic acids and other low abundance components in native bone and osteosarcoma extracellular matrix by isotope enrichment and DNP-enhanced NMR

Abstract: Towards elucidating their biological roles in intact tissue, DNP NMR reveals nucleic acids, and other important low abundance biomolecules in a complex biomaterial, bone, and in cancer extracellular matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…In this case, the need to impregnate the sample by a radical solution raises the question of the choice of the radical/solvent couple, the goal being to avoid (or minimize) any structural changes within the biological sample. When looking at the few studies reported so far, most bone sample preparations involved an AMUPol biradical solution in H2O/D2O, [81][82][83] leading to 13 C DNPenhancement factors between ~ 20 and 60 ( Figure 6). It is worth noting that these impregnation procedures differed slightly in terms of AMUPol concentration (between 12 and 20 mM), D2O/H2O ratio, duration of the impregnation, and size of the bone particles studied.…”
Section: Considerations On Sample Preparation For Nmr and Dnp Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the need to impregnate the sample by a radical solution raises the question of the choice of the radical/solvent couple, the goal being to avoid (or minimize) any structural changes within the biological sample. When looking at the few studies reported so far, most bone sample preparations involved an AMUPol biradical solution in H2O/D2O, [81][82][83] leading to 13 C DNPenhancement factors between ~ 20 and 60 ( Figure 6). It is worth noting that these impregnation procedures differed slightly in terms of AMUPol concentration (between 12 and 20 mM), D2O/H2O ratio, duration of the impregnation, and size of the bone particles studied.…”
Section: Considerations On Sample Preparation For Nmr and Dnp Analysesmentioning
confidence: 99%
“…2D 13 C-13 C DQ-SQ, and DARR-assisted 15 N- 13 C correlations) to highlight a number of major features concerning the organic component of bone and the development of the tissue. These include (i) the potential importance of poly-ADP-ribose in the extacellular matrix for developing bone, which is likely to play a role in calcification, [86,88] (ii) the detection in native intact bone of nucleic acids and other low-abundant components (like cholines from phospholipid headgroups, as well as histidinyl and hydroxylysyl groups), [83] and (iii) the in-depth study of collagen structure and flexibility. [79] Organic-mineral interfaces in bone have also been the focus of much attention.…”
Section: Advances In Nmr and Dnp Analyses Of Bone Structurementioning
confidence: 99%
“…In the 1D 1 H– 15 N CPMAS spectrum of the bone (Figure A), we have assigned the resonances exclusively from Gly N (109.2 ppm), Hyp/Pro N (129.9 ppm), Arg Nε (82.5 ppm), Arg Nη­(71.0 ppm), Lys Nζ (38 and 31.7 ppm), and Trp Nε (138 ppm). Similarly, the resonances exclusively from Gly N (109.2 ppm), Hyp/Pro N (129.8 ppm), Arg Nε (82.3 ppm), Arg Nη­(71.3 ppm), Lys Nζ (37.1 and 29.1 ppm), and Trp Nε (138 ppm) are assigned for the 1D 1 H– 15 N CPMAS spectrum of the cartilage (Figure C). , In both matrices, 15 N resonances from collagen protein are observed at nearly the same chemical shift except for Lys Nζ (38 and 31.7 ppm), evidencing a different chemical environment around the Lys residue. Remarkable sensitivity enhancement in natural-abundance 1D 1 H– 15 N CPMAS spectra directs us to record further the 2D 1 H– 15 N HETCOR spectra of both samples.…”
Section: Resultsmentioning
confidence: 85%
“…We have assigned the resonances originating exclusively from the Pro/Hyp backbone at 121.6 ppm, Gly at 108 ppm, [ 50 ] and 15 N side chains of histidine and arginine. [ 47 ] Resonances from arginine (84.4 ppm and 70.8 ppm) and lysine (32 ppm) were also assigned, [ 51 ] which were not possible to detect in the conventional solid‐state NMR CPMAS spectrum of 15 N (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, MAS‐DNP solid‐state NMR methods are highly efficient in sensitivity enhancement for elucidating the structural details of the biological system, such as bone at natural isotopic abundance. [ 51,57 ] Despite the advantage of sensitivity enhancement, due to the requirement of the low‐temperature, molecular motion is significantly slowed down, and molecules are trapped in a range of conformations that leads to slightly different chemical shifts along with the broadening of the signals and a reduction in the resolution. Moreover, with the use of stable biradical for doping the sample, DNP‐enhanced ssNMR cannot be considered a noninvasive technique.…”
Section: Resultsmentioning
confidence: 99%